Pengaruh Pemberian Reward Sticker Emoticon Terhadap Percaya Diri Anak Usia 5-6 Tahun Di TK Sentuhan Kasih Abadi Tarutung - Hana Sitorus; Endang Junita Sinaga; Julita Herawati P (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to determine the effect of giving emoticon sticker rewards on the self-confidence of children aged 5-6 years. The method used in this research is a quantitative research method of the pre-experimental design type in the form of